2006
DOI: 10.1242/jcs.02773
|View full text |Cite
|
Sign up to set email alerts
|

The major vault protein is responsive to and interferes with interferon-γ-mediated STAT1 signals

Abstract: These data further substantiate that the vault particle functions as a general interaction platform for cellular signaling cascades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
90
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 37 publications
5
90
0
Order By: Relevance
“…Several recent studies have suggested that MVP is involved in cell survival following stress or damage, 34,35 but apparently plays no role in development as MVP knockout mice exhibit no discernible developmental abnormalities. 35 We have recently shown that increased levels of Bcl-2 contribute to apoptotic resistance in senescent HDFs.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have suggested that MVP is involved in cell survival following stress or damage, 34,35 but apparently plays no role in development as MVP knockout mice exhibit no discernible developmental abnormalities. 35 We have recently shown that increased levels of Bcl-2 contribute to apoptotic resistance in senescent HDFs.…”
Section: Discussionmentioning
confidence: 99%
“…MVP/vaults have been associated with multidrug resistance (21)(22)(23), nuclear-cytoplasmic transport (24), innate immunity (25), autophagy (26), and signal transduction pathways (27)(28)(29)(30)(31); however, the precise function of MVP/ vault remains enigmatic. Our previous work indicating MVPinduced type I IFN production upon hepatitis C virus infection uncovers a new role of MVP in modulating innate immunity during viral infection (32).…”
mentioning
confidence: 99%
“…Similarly, Siva et al (51) demonstrated that the upregulation of MVP is not sufficient to confer an MDR phenotype. In addition, recent studies have correlated MVP with several signaling pathways (52)(53)(54)(55)(56) and immune responses (57)(58)(59)(60), which imply that the function of MVP may be more complex than expected. Thirdly, the inability to find an association between variants of the MVP gene and platinum resistance or survival in the present study may be due to the limited number of patients enrolled in the study, since the number of patients in the subgroup was below the statistical threshold.…”
Section: Discussionmentioning
confidence: 99%